Cardio- and nephroprotective effects of fractions isolated from Lycium barbarum (goji berry) in models of cardio- and nephrotoxicity in rats - Nadezhda Hvarchanova; Stanila Stoeva; Maya Radeva-Ilieva; Iliya Zhelev; Marieta Georgieva; Deyan Dzhenkov; Kaloyan D. Georgiev (Biotechnology & Biotechnological Equipment)
The aim of the present study was to identify agents that reduce the anthracyclines-induced cardiovascular and renal damage and have the potential to enhance their therapeutic effects. Three fractions of Lycium barbarum (Goji berry), pectin-free, polysaccharide and a combination of the two (1:1, w/w), were tested on rat models of doxorubicin (DOX)-induced cardio- and nephrotoxicity. They were administered p.o. as doses of 2 mg/kg. DOX was applied at a cumulative dose of 20 mg/kg (i.p.). Different biomarkers for cardiotoxicity (creatine kinase, creatine kinase-MB fraction, aspartate aminotransferase, lactate dehydrogenase), nephrotoxicity (creatinine, blood urea nitrogen, uric acid) and the serum potassium levels were evaluated. Histological analysis of hearts and kidneys was performed. The male Wistar rats treated only with DOX showed a drastic increase in all biomarkers for toxicity. Meanwhile, in all cohorts receiving simultaneously any of the plant fractions, the biomarkers for heart and kidney tissue damage were significantly reduced (p < 0.001 for uric acid; p < 0.01 for other parameters). Intriguingly, the pectin-free fraction and the combined one showed the most pronounced decrease in the indicators for toxicity. Histological findings also confirmed these observations, suggesting that the fractions in question need to be investigated as potential enhancers of anthracyclines’ pharmacodynamic effects.